Answer:
B
Step-by-step explanation:
-2-(-4) = -2 + 4
B shows subtracting 2 to the left then adding 4 to the right.
Answer:
x = -5 and y = 3
Step-by-step explanation:
There are two equations :
3x − 2y = −21 ....(1)
2x + 5y = 5 ......(2)
Multiply equation (1) by 2 and equation (2) by 3.
6x - 4y = -42 ...(3)
6x + 15y = 15 ....(4)
Subtract equation (4) from (3) :
6x - 4y - (6x + 15y) = -42 -15
-4y -15y = -57
-19y = -57
y = 3
Put y = 3 in equation (2) :
2x + 5(3) = 5
2x = 5-15
2x = -10
x = -5
So, the value of x is (-5) and y = 3.
Answer: 78
Step-by-step explanation:
6(4+9)
use foil to distribute the 6 to the 4 and 9
6×4 + 6×9
24 + 54
⇒ 78
The answer is: 24√6 .
_______________________________
The question asks:
_______________________________
"<span>What is the product of (3√8)(4√3)? Simplify your answer/
First, let us simplify: "</span>√8"
"√8 = √4*√2 = 2√2 ;
So, "3√8 = 3*2√2 = 6√2" .
So, "what is the product of "(3√8)(4√3)"?
Rewrite, replacing the "(3√8)" with "6<span>√2" ; as follows:
</span>6√2* 4√3 = 6*4 *√2*√3 = 24 *√(2*3) = 24√6 .
______________________________________